Model Pengembangan Produktivitas Perajin Industri Bidai Di Wilayah Perbatasan - Iman Kalis, Maria Christiana (Fakultas Ekonomi dan Bisnis, UNTAN, 2015)
Social and economic phenomena seen among the various efforts to develop culture-basedhandicraft industry. Several groups of small business industry looks continue to live but with thecondition that no maximum. The quality of labor in the industry is determining the level ofproductivity of the industry output.Industry sector is the sector that absorbs labor andemployment issues is a crucial issue especially when it comes to productivity. This is due to theproductivity can be achieved when workers have a willingness to work with a boost in selfworker.Work will occur if the labor needs of both physical and non-physical being met. In thisstudy, the element of productivity is measured is associated with the quality of workerseducational level, expertise, skills and labor in handicraft industry studied where this industry isbuilt upon the characteristics of the local culture by low adoption of technologies that are likelyto improving the entrepreneurial skills.